THE RELATIONSHIP BETWEEN KNOWLEDGE OF SCHIZOPHRENIA AMONG FAMILY AND RELAPSE ON EARLY PSYCHOSIS PATIENT IN YOGYAKARTA - , AMIRA AUNI BINTI ASMADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Schizophrenia is a major mental illness whose mechanism is still unknown. Research suggests that schizophrenia has something to do with problems with brain chemistry and brain structure. Early in detection and intervention can help in reducing the risk of having relapse. Delay in detection and intervention represents a public health crisis. Knowledge of family in schizophrenia is needed to provide a better care for the patient and can help in reducing the number of relapse. Objective: Determine the relationship between knowledge of schizophrenia among family and relapse in early psychosis patients. Method: A cross-sectional study carried out to 100 respondents which comprise of patientâs family member. The patients are already having their treatment from Dr Sardjito Hospital, District Hospital in Yogyakarta that has psychiatrics, Ghrasia Hospital and Puri Nirmala Hospital. The data obtained from family member on their knowledge of schizophrenia by filling in the KAST questionnaire followed by asking about the patientâs relapse. Then, the result is analyzed. Results: Families with low level of knowledge (20%) has higher percentage of relapse compared to high level of knowledge (5,5%). Coefficient contingency is 0,217 with p=0.030. The 95% CI is 0,000 to 0,063. Conclusion: There is a statistically significant difference on the relapse between high and low level of knowledge about schizophrenia among patientsâ family.